P04.19 Alcohol involvement in sexual behaviour and adverse sexual health outcomes in early middle age. (13th September 2015) - Connor, JL; Kydd, R; Dickson, N
Abstract : Introduction: Research on alcohol and sexual behaviour has focused on young adults or high-risk groups, showing alcohol use contributing to riskier sexual choices. Adults now in early midlife have been exposed to heavier drinking norms than previously, raising questions about effects on sexual well-being. We examined self-reported use and consequences of alcohol in sexual contexts, and its association with usual drinking pattern at age 38, and also associations of heavy drinking occasion (HDO) frequency with number of sexual partners, sexually transmitted infection (STI), and termination of pregnancy (TOP), from 26–32 and 32–38 years of age. Methods: Members of the Dunedin Study birth cohort answered computer-presented questions about sexual behaviour and outcomes, and interviewer-administered alcohol consumption questions, at age 26, 32 and 38 years. Results: Response level was >90% at each assessment. At 38, drinking before or during sex in the previous year was common (8.2% of men; 14.6% of women reported "usually/always"), and unwanted consequences were reported by 13.5% of men and 11.9% of women, including regretted sex or failure to use contraception or condoms. Frequent heavy drinkers were more likely to "use alcohol to make it easier to have sex" and regret partner choice, particularly women. Heavy drinking frequency was strongly associated with partner numbers for men and women at 32, but only for women at 38. Significantly higher odds of STIs amongst the heaviest drinking men, and TOPs amongst the heaviest drinking women were seen at 32–38. Conclusion: Alcohol involvement in sex continues beyond young adulthood where it has been well documented, and is common at 38. Women appear to be more affected than men, and heavy drinking is associated with poorer outcomes for both. Improving sexual health and wellbeing throughout the life course needs to take account of the role of alcohol in sexual behaviour. Disclosure of interest statement: This work was supported by the Health Research Council of New Zealand [12/1086]. The authors have no conflicts of interest.